CLASSIFICATION OF ELECTROCARDIOGRAM (ECG) WAVES OF HEART DISEASE USING THE XGBOOST METODE METHOD - Butarbutar, Serly Yunarti; Napitupuluh, Christian Deniro; Ginting, Nessa Sanjaya; Indra, Evta; Sitanggang, Delima (Sean Institute, 2022)
CLASSIFICATION OF ELECTROCARDIOGRAM (ECG) WAVES OF HEART DISEASE USING THE XGBOOST METODE METHOD